Analysis of the Impact of the Formation of a Holding Company for Private Insurance Companies in Indonesia - Hutama P, M. Bagas; Suryono, Arief (MultiTech Publisher, 2024)
BUMN holding, including BUMN holding in the insurance and guarantee sector, is a form of corporate restructuring to improve company performance through the consolidation of several BUMNs. Holding in the insurance and guarantee sector was formed based on Government Regulation Number 20 of 2020 concerning Additional State Capital Participation in the Share Capital of the Company PT Bahana Pembinaan Usaha Indonesia which stipulates PT Bahana Pembinaan Usaha Indonesia as the holding company. The problem in this research is how the legal regulation of BUMN holding in the insurance and guarantee sector is in the national legal system in Indonesia and what are the responsibilities of BUMN holding in the insurance and guarantee sector towards its subsidiaries. Based on the research results, it can be seen that the background to the establishment of BUMN holding in the insurance and guarantee sector is based on juridical factors, namely in Law Number 19 of 2003 concerning State-Owned Enterprises, Law Number 40 of 2007 concerning Limited Liability Companies, and Government Regulation Number 20 of 2020 concerning Additional State Capital Participation in the Share Capital of the Limited Liability Company PT Bahana Pembinaan Usaha Indonesia.